2019
DOI: 10.1038/s41598-019-53101-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status modifies pregnane X receptor regulated transcriptome

Abstract: Pregnane X receptor (PXR) regulates glucose and lipid metabolism, but little is known of the nutritional regulation of PXR function. We investigated the genome wide effects of the nutritional status on the PXR mediated gene regulation in the liver. Mice were treated with a PXR ligand pregnenolone 16α-carbonitrile (PCN) for 4 days and subsequently either fasted for 5 hours or after 4-hour fast treated with intragastric glucose 1 hour before sample collection. Gene expression microarray study indicated that PCN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Feeding may affect metabolic responses and a recent study utilizing metabolomics approach similar to this study reported the effect of glucose feeding (Wang et al, 2019). Moreover, we have reported the modifying effect of glucose feeding on PXR function in mouse liver (Hassani‐Nezhad‐Gashti et al, 2019). To analyse dynamics of the lipidome during glucose challenge in response to rifampicin, we utilized a third clinical study, Rifa‐2, with oral glucose tolerance test (oral glucose tolerance test) in 12 healthy volunteers before and after 1‐week rifampicin dosing.…”
Section: Resultsmentioning
confidence: 99%
“…Feeding may affect metabolic responses and a recent study utilizing metabolomics approach similar to this study reported the effect of glucose feeding (Wang et al, 2019). Moreover, we have reported the modifying effect of glucose feeding on PXR function in mouse liver (Hassani‐Nezhad‐Gashti et al, 2019). To analyse dynamics of the lipidome during glucose challenge in response to rifampicin, we utilized a third clinical study, Rifa‐2, with oral glucose tolerance test (oral glucose tolerance test) in 12 healthy volunteers before and after 1‐week rifampicin dosing.…”
Section: Resultsmentioning
confidence: 99%
“…Although significant levels of several K vitamers (particularly MK-4) were found in tissues, like mammalian thyroid and adrenal gland [ 9 , 16 ], and ggcx , vkorc1 and vkorc1l1 were reported to be expressed in the adrenal gland of male and female mice [ 92 ], little is known regarding how VK might affect thyroid and adrenal hormones signaling. While PXR-regulated transcriptome is dependent on the nutritional status, affecting thyroid hormone metabolism II in mice [ 156 ], several studies have shown that PXR plays an important role in adrenal steroid hormone homeostasis. Activation of PXR markedly increases plasma concentrations of corticosterone and aldosterone, the primary glucocorticoid and mineralocorticoid in rodents, being associated to the activation of adrenal steroidogenic enzymes, including CYP11A1, CYP11B1, CYP11B2, and HSD3B2 [ 157 ].…”
Section: The Impact Of Vitamin K In Reproductionmentioning
confidence: 99%
“…As one example, exposure to statins is a known risk factor for type 2 diabetes (e.g., [ 234 ]). Although statins can activate CAR modestly [ 235 ], they affect PXR more strongly [ 236 ]. Other mechanisms underlying the statin-elicited increase in blood glucose levels likely exist [ 237 ].…”
Section: Metabolic Effects Of Edc Classes Potentially Mediated By mentioning
confidence: 99%